2019
DOI: 10.1128/aem.01742-19
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies and Intraspecies Signals Synergistically Regulate Lysobacter enzymogenes Twitching Motility

Abstract: The twitching motility of bacteria is closely related to environmental adaptability and pathogenic behaviors. Lysobacter is a good genus in which to study twitching motility because of the complex social activities and distinct movement patterns of its members. Regardless, the mechanism that induces twitching motility is largely unknown. In this study, we found that the interspecies signal indole caused Lysobacter to have irregular, random twitching motility with significantly enhanced speed. Deletion of qseC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…For instance, twitching motility is required for colonization and infection of phytopathogenic fungi and oomycetes in Lysobacter spp. ( Patel et al, 2011 ; Tomada et al, 2017 ), and it seems to be a DSF-dependent trait in L. brunescens and L. enzymogenes ( Qian et al, 2013 ; Feng et al, 2019 ; Ling et al, 2019b ). Interestingly, upregulation of T4P by GLY and BUT came along with increased antimicrobial activity, suggesting that microbial partners producing this kind of diffusible communication signals might encourage AZ78 to form a stable community and stimulate traits responsible for disease suppressiveness in soils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, twitching motility is required for colonization and infection of phytopathogenic fungi and oomycetes in Lysobacter spp. ( Patel et al, 2011 ; Tomada et al, 2017 ), and it seems to be a DSF-dependent trait in L. brunescens and L. enzymogenes ( Qian et al, 2013 ; Feng et al, 2019 ; Ling et al, 2019b ). Interestingly, upregulation of T4P by GLY and BUT came along with increased antimicrobial activity, suggesting that microbial partners producing this kind of diffusible communication signals might encourage AZ78 to form a stable community and stimulate traits responsible for disease suppressiveness in soils.…”
Section: Discussionmentioning
confidence: 99%
“…rhizosphere competence and their ability to control plant pathogens. Indeed, it has been shown that DSFs, DFs, and IND regulate the biosynthesis of the heat-stable antifungal factor (HSAF), a potent antifungal compound, and twitching motility in Lysobacter enzymogenes ( Qian et al, 2013 ; Han et al, 2017 ; Su et al, 2017 ; Feng et al, 2019 ). However, with the only exception of the involvement of DSFs and AHLs in Lysobacter brunescens behavior ( Ling et al, 2019a , b ), a complete overview of the overall effect of diffusible communication signals in the ecology of Lysobacter spp.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, twitching motility is required for colonization and infection of phytopathogenic fungi and oomycetes in Lysobacter spp. [55, 56] and it seems to be a DSF-dependent trait in L. brunescens and L. enzymogenes [9, 20, 21]. Interestingly, up-regulation of T4P by GLY and BUT came along with increased antimicrobial activity, suggesting that AZ78 might colonize new niches and form a stable community to outcompete other (micro)organisms upon the perception of these DCSs.…”
Section: Discussionmentioning
confidence: 99%
“…This ability mainly relies on the release of lytic enzymes and antibiotics like the Heat Stable Antifungal Factor (HSAF), which are toxic to phytopathogenic (micro)organisms [16, 17]. In L. enzymogenes DSFs, DFs and IND regulate HSAF biosynthesis [9, 18, 19] and twitching motility [20]. Furthermore, IND reverses the intrinsic antibiotic resistance of L. enzymogenes through the two-component regulatory system QseC/QseB [19, 20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation